Multiliteracy-Based Learning in Early Childhood Education in the Era of Society 5.0 - Kandi kandi (Pt. Anagata Sembagi Education, 2026)
The transformation of early childhood education in the era of Society 5.0 requires the integration of multiliteracy to support children’s holistic development. Multiliteracy encompasses not only basic literacy but also digital, multilingual, ecological, and moral-religious competencies, which are essential in responding to rapid technological advancements while maintaining humanistic values. This study aims to analyze and develop a multiliteracy-based learning framework in early childhood education that is adaptive to the demands of Society 5.0. This research employs a qualitative approach with a descriptive-analytical design, combining library research and field study. Data were collected through in-depth interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion verification with triangulation techniques to ensure validity. The findings reveal that multiliteracy-based learning has been partially implemented through digital media, project-based learning, STEAM approaches, and integration of cultural and religious values. However, challenges persist, including limited infrastructure, low teacher digital competence, uneven implementation, and weak institutional management. The discussion highlights the need for a balanced integration of technology and character education within a structured multiliteracy framework. In conclusion, multiliteracy-based learning in early childhood education must be developed through a holistic, adaptive, and human-centered approach that integrates technology, pedagogy, and cultural values to prepare children for the complexities of Society 5.0